2014
DOI: 10.2113/gsjfr.44.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Living (Stained) Deep-Sea Foraminifera Off Hachinohe (Ne Japan, Western Pacific): Environmental Interplay in Oxygen-Depleted Ecosystems

Abstract: Live (Rose-Bengal stained) deep-sea foraminiferal faunas have been studied at five stations between 500-2000-m depth along the NE Japanese margin (western Pacific) to understand how complex environmental conditions (e.g., oxygen depletion, organic matter) control their structure (i.e., diversity, standing stocks, and microhabitats). All stations are characterized by silty sediments with no evidence of recent physical disturbances. The three stations located between 760-1250 m are bathed by dysoxic bottom water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 96 publications
(183 reference statements)
3
37
1
Order By: Relevance
“…Minima were recorded on 24 June (178 μM) and on 19 August (152 μM). Because the DO shows a decreasing trend from the sea surface to 1000 m depth in the area off Sanriku (Ogura 1970;Fontanier et al 2014;Nomaki et al 2015), we inferred that the DO decreases that we observed were caused by intermittent upwelling of deeper water. During the periods when DO was low, σ t was increased.…”
Section: Water Mass Changes At the Upper Slope Sitementioning
confidence: 65%
See 1 more Smart Citation
“…Minima were recorded on 24 June (178 μM) and on 19 August (152 μM). Because the DO shows a decreasing trend from the sea surface to 1000 m depth in the area off Sanriku (Ogura 1970;Fontanier et al 2014;Nomaki et al 2015), we inferred that the DO decreases that we observed were caused by intermittent upwelling of deeper water. During the periods when DO was low, σ t was increased.…”
Section: Water Mass Changes At the Upper Slope Sitementioning
confidence: 65%
“…The upper slope site is in an active fishery area, and trawling is frequently conducted around its water depth, except between July and August. The bathyal site is within the O 2 -depleted zone of the North Pacific (DO < 45 μM; found at water depths from 700 to 1300 m; Ogura 1970;Fontanier et al 2014). Although there is little fishery activity at the bathyal depth, some important fishery resources such as Sebastolobus macrochir is distributed at that depth (e.g., Hattori et al 2007;Sakaguchi-Orui et al 2014), and knowledge of benthic habitats is essential information for understanding the ecology of such fish.…”
Section: Seafloor Monitoring and Ctd Sitesmentioning
confidence: 99%
“…Bolivina spissa, nearly only found from cluster Ib, has been reported in the oxygen minimum zone of the Pacific Ocean (Ingle et al, 1980;Quinterno and Gardner, 1987;Fontanier et al, 2014). Fontanier et al (2014) studied living benthic foraminiferal assemblages between 500-2000 m depth off Hachinohe (northeast Japan). They reported that the B. spissa distribution is restricted to stations bathed by dysoxic waters between 760-15 1250 m depth.…”
Section: Benthic Foraminiferal Faunal Change Of the Deep-sea Floor DImentioning
confidence: 99%
“…The tsunami disturbances also affected benthic communities on the continental shelf and upper continental slope (Toyofuku et al, 2014). Five months after the tsunami, the shelf ecosystems off Shimokita (northeast Japan) were characterized by high 10 species diversity and did not show a reduction in density, but an opportunistic fauna dominated the deeper site (211 m depth).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation